Enhancing Thermodynamics Education: Insights from Student Knowledge Assessments on (Ir)reversible Processes and (Non)equilibrium Phenomena - Ivana Weber; Tina Borić; Josipa Mardešić; Ante Bilušić; Larisa Zoranić (Education Sciences)
Thermodynamics is a theory based on phenomenological premises and has wide applicability in science and technology. However, it remains one of the most challenging subjects to understand and teach, which makes it an excellent candidate for research and development of teaching methods. In this research, a questionnaire was used to evaluate the current knowledge of Bachelor’s and Master’s physics students, analyzing their immediate understanding of the topic and exploring their reasoning and thought processes. The questionnaire is divided into three sections which sequentially examine high school knowledge of entropy and thermodynamics; understanding of (ir)reversible processes related to energy and entropy change; and the distinction between equilibrium and nonequilibrium states. Based on the analysis of the results, we identified difficulties in understanding and articulating and applying the learned concepts. In particular, misunderstandings of entropy changes in isothermal processes and isolated systems are observed among students at all levels. Additionally, students find it difficult to distinguish between the contributions of energy and entropy changes to a system and its environment in the processes. The difficulty in defining (non)equilibrium states is present among Bachelor’s second-year physics students. To address these challenges, we propose adjustments to the teaching approach, including discussions about entropy sources and process (ir)reversibility, incorporating more theoretical and everyday examples of various processes and (non)equilibrium states and allowing more time for student discussions.